EMOTIONAL INTELLIGENCE EDUCATION VERSION OF THE QUR'AN - Abdul rohman (LTN NU Sulawesi Tengah, 2023)
Al-Qur'an is one of the sources of Islamic law which is full of wisdom other than As-Sunnah (Hadith). The values contained in it always inspire readers and